Experiences of Caregivers and Relatives in Public Nursing Homes - Häggström, Elisabeth (Nursing ethics, 2007)
The aim of the present study was, by means of discussion highlighting ethical questions and moral reasonings, to increase understanding of the situations of caregivers and relatives of older persons living in a public nursing home in Sweden. The findings show that these circumstances can be better understood by considering two different perspectives: an individual perspective, which focuses on the direct contact that occurs among older people, caregivers and relatives; and a societal perspective, which focuses on the norms, values, rules and laws that govern a society. Relatives and caregivers thought that the politicians were sending out mixed messages: they were praising caregivers and relatives for their efforts, but at the same time the public health care sector was subjected to significant cutbacks in resources. Both caregivers and relatives were dissatisfied and frustrated with the present situation regarding the care of older persons in public nursing homes.